Global Economic Prospects, June 2021 - World Bank (Washington, DC: World Bank, 2021)
The world economy is experiencing a very strong but uneven recovery, with many emerging market and developing economies facing obstacles to vaccination. The global outlook remains uncertain, with major risks around the path of the pandemic and the possibility of financial stress amid large debt loads. Policy makers face a difficult balancing act as they seek to nurture the recovery while safeguarding price stability and fiscal sustainability. A comprehensive set of policies will be required to promote a strong recovery that mitigates inequality and enhances environmental sustainability, ultimately putting economies on a path of green, resilient, and inclusive development. Prominently among the necessary policies are efforts to lower trade costs so that trade can once again become a robust engine of growth. This year marks the 30th anniversary of the Global Economic Prospects. The Global Economic Prospects is a World Bank Group Flagship Report that examines global economic developments and prospects, with a special focus on emerging market and developing economies.